The Influence of Curriculum Reforms on Teaching Practices and Student Learning Outcomes in Educational Development - Danial, Muhammad; Ardi, Ardi; Hidayatullah, Syarif (Educia Journal, 2024)
This study explores the role of curriculum reforms in education development, focusing on the perceptions and experiences of teachers, administrators, and students in schools that have undergone recent curriculum changes. Using a qualitative case study approach, the research involved semi-structured interviews, focus group discussions, and document analysis to gather data on the impact of the reforms. The findings reveal that while curriculum reforms have led to increased student engagement and the promotion of student-centered learning, challenges such as insufficient teacher training, inadequate resources, and resistance to change hindered their effective implementation. Teachers reported a lack of professional development and resources necessary to support the new curriculum, which affected their ability to fully integrate the reforms into their teaching practices. Students, on the other hand, expressed increased interest in subjects that employed project-based and collaborative learning methods, although some struggled with the self-regulation required in a more independent learning environment. This study contributes to existing literature by addressing gaps in teacher preparedness, resource allocation, and the varying outcomes of student-centered learning. The research underscores the importance of comprehensive teacher training, adequate resources, and inclusive reform processes to ensure the success of curriculum changes in promoting quality education.